2022
DOI: 10.3390/plants11060713
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Associations among Grain Yield and Quality Traits in Quality Protein Maize (QPM) and Non-QPM Hybrids

Abstract: Maize (Zea mays L.) is the main staple cereal food crop cultivated in southern Africa. Interactions between grain yield and biochemical traits can be useful to plant breeders in making informed decisions on the traits to be considered in breeding programs for high grain yield and enhanced quality. The objectives of this study were to estimate the heritability of grain yield and its related traits, as well as quality traits, and determine the association between quality protein maize (QPM) with non-QPM crosses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
4
9
0
1
Order By: Relevance
“…Similar findings were reported by Amegbor et al[52], Devasree et al[46], Pandey et al[53], Kinfe et al[43], Kote et al[46], Reddy et al[36], Kumar et al[54], Selvaraj et al[5], Saidaiah et al[44], Geetha et al[55]. Similar findings were reported by Devasree et al[56], Pandey et al[53], Kote et al[36], Selvaraj et al[5], Saidaiah et al[44], Singh et al[38], Kinfe et al[43], Reddy et al[36], Kumar et al[54], Geetha et al[55].…”
supporting
confidence: 92%
“…Similar findings were reported by Amegbor et al[52], Devasree et al[46], Pandey et al[53], Kinfe et al[43], Kote et al[46], Reddy et al[36], Kumar et al[54], Selvaraj et al[5], Saidaiah et al[44], Geetha et al[55]. Similar findings were reported by Devasree et al[56], Pandey et al[53], Kote et al[36], Selvaraj et al[5], Saidaiah et al[44], Singh et al[38], Kinfe et al[43], Reddy et al[36], Kumar et al[54], Geetha et al[55].…”
supporting
confidence: 92%
“…The cultivars Simpatico, Arifiye, SY-Antex, Kolessaus, and Sakarya were prominent in terms of many quality traits such as PC, FC, AC, TF, TW, ADF, K, P, Mg, Fe, Zn, and Mn. This result is partly consistent with a previous report (Amegbor et al, 2022). Yousaf et al (2021) showed the negative association between starch and fat content.…”
Section: Biplot Analysissupporting
confidence: 94%
“…In our study, traits which are investigated for variability in BC 1 F 2:3 population are protein content, ear length (cm), ear width (cm), kernel rows/ear and test weight (g). The results are consistent with those of earlier reports ofAmegbor et al (2022). Cluster I having Teosinte is entirely different from remaining 5 clusters which is represented in dendrogram (Fig:5).…”
supporting
confidence: 92%